Politeness Strategies Used in the Interview between Amna Nawaz and the Iranian Foreign Minister on Iran vs the USA-Israel War - Zelina, Felicia Farrah; Hkikmat, Mahi M.; Wardoyo, Cipto (Journal of Language and Literature Studies, 2026)
Political interviews frequently address sensitive issues, particularly in high-stakes contexts such as war, diplomacy, and international conflict. In such situations, speakers are frequently confronted with face-threatening questions that challenge their authority and institutional image. Therefore, politeness strategies are applied to minimize face-threatening acts (FTAs) and maintain harmonious interaction. This study examines the application of politeness strategies by both participants and explains their implications in the interaction. The interview discussed the ongoing war between Iran versus the United States of America (USA) and Israel. This research adopts Brown and Levinson (1987) politeness strategies framework and applied qualitative content analysis as the method. This study uses documentation technique to analyze the data. The data were collected from the PBS NewsHour official YouTube channel. The  findings show that there are 85 utterances contain politeness strategies in the interaction. Amna Nawaz produced 29 utterances containing politeness strategies and predominantly employed Negative Politeness with 15 occurrences. In contrast, Abbas Araghchi produced 56 utterances and mainly used Bald on Record, accounting for 37 occurrences. The predominant strategy used by Amna Nawaz used to minimize imposition and maintain respect while asking critical questions. In contrast, the Iranian Foreign Minister predominantly applied bald on-record strategy. It was used to provide direct and clear responses that represented Iran’s official stance. These patterns reflect their different communicative roles. The interviewer predominantly use negative politeness strategies to mitigates face-threatening questions while the interviewee adopts a direct and firm response to defend institutional positions.